AMELIORATING EFFECT OF HAWTHORN (CRATAEGUS OXYACANTHA) AND PHYSICAL EXERCISE ON ACUTE PENICILLIN INDUCED SEIZURES IN GERBILS - Cakir, Serkan; Orallar, Hayriye; Cetinkaya, Ayhan; Kayacan, YÄ±ldÄ±rÄ±m; Onal, Ali Can; Yildirim, Arzu; Beyazcicek, Ersin; Benek, Selim; Ozkan, Murat; Ince, Omer Baris; Okur, Nezih (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
The aim of the present study was to assess the effect of Hawthorn (Crataegus oxyacantha) and physical activity. We studied its effect on penicilline induced epilepticus (Pie) in gerbils. Pie was induced by administration of penicilline G (500 IU, ip). The gerbils were divided randomly in four groups (6 animals per each group) and studied as described below: 1) Control group 2) Exercise group (30 min/each day for 8 weeks) (Eg) 3) Extract group, 50mg/kg/day/animal in 1 ml saline, 3 h prior to exercise (Exe) 4) Exercise+Extract + (Exe+Ex). The severity of Pie was observed and recorded. The means of latencies (Mean±SE) were 236±45, 369±36, 386±58 and 433±37 ms in groups of control, Exe, Ex, and Exe+Ex respectively. The mean spike latency significantly (P=0,033 F=3,560) decreased in Exe, Ex and Exe+Ex when compared control. Although spike frequency significantly (P<0.05) diminished in groups of Exe and Ex, no significant decrease was observed in control and Exe+Ex. Similar trend was seen for amplitude values. Spike amplitude values were determined to be significantly (P<0.05) lower than those of control and Exe+Ex.